Avicenna’s Shifāʾ (Sufficientia): in Defense of Medieval Latin Translators - Saliba, George (Der Islam, 2017)
This article explores the reasons why medieval Latin translators used the term Sufficientia to translate the title of Avicenna’s philosophical work, known in Arabic as al-shifāʾ and did not use instead terms like “healing” or “cure”, which are now frequently used. The article demonstrates that those medieval Latin translators may after all have had a better understanding of classical Arabic linguistic sources than they are usually credited for, and were thus fully justified to opt for the translation they used.